2022
DOI: 10.29133/yyutbd.1139773
|View full text |Cite
|
Sign up to set email alerts
|

Quality Proficiency to Crop, Soil and Irrigation System of Recycled Wastewater from the Van/Edremit Wastewater Treatment Plant

Abstract: Increasing pressure on water resources in the world has revealed the necessity of using marginal water resources in irrigation. With the use of wastewater, which is one of the marginal water resources, the pressure on freshwater resources is alleviated, the discharge problems of wastewater are solved, and soil and crop productivity increase with the high nutritive effect of wastewater. However, salinity, heavy metals, some harmful chemicals, and the pathogen risks of wastewater should not be ignored. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The ndings indicate that we can make signi cant progress in using wastewater for farming with the improvements in treatment techniques that we already have (Kesari et al, 2021). But, to make sure that wastewater irrigation is safe and can continue in the long term, we need to check the quality of the water and inspect the soil, crops, and irrigation systems (Yerli and SAHİN, 2022). The ndings revealed that over a long period of time, soils watered with wastewater contain a high amount of heavy metals compared to elds watered with fresh water.…”
Section: Introductionmentioning
confidence: 99%
“…The ndings indicate that we can make signi cant progress in using wastewater for farming with the improvements in treatment techniques that we already have (Kesari et al, 2021). But, to make sure that wastewater irrigation is safe and can continue in the long term, we need to check the quality of the water and inspect the soil, crops, and irrigation systems (Yerli and SAHİN, 2022). The ndings revealed that over a long period of time, soils watered with wastewater contain a high amount of heavy metals compared to elds watered with fresh water.…”
Section: Introductionmentioning
confidence: 99%